Die wiskundige modellering van Guerrilla-oorlogvoering - Steenkamp, D. J.(Dawid Johannes),1964- (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M. Sc.) -- Universiteit van Stellenbosch, 1988.